Heartbreak : a personal and scientific journey - Williams, Florence, 1967- (W. W. Norton & Company, 2022)
"Florence Williams explores the fascinating, cutting-edge science of heartbreak while seeking creative ways to mend her own. When her twenty-five-year marriage unexpectedly falls apart, journalist Florence Williams expects the loss to hurt. What she doesn't expect is that she'll end up in the hospital, examining close-up the way our cells listen to loneliness. She travels to the frontiers of the science of "social pain" to learn why heartbreak hurts so much and why so much of the conventional wisdom about it is wrong. Searching for insight as well as personal strategies to game her way back to health, Williams tests her blood for genetic markers of grief, undergoes electrical shocks in a laboratory while looking at pictures of her ex, and ventures to the wilderness in search of awe as an antidote to loneliness. For readers of Wild and Lab Girl, Heartbreak is a remarkable merging of science and self-discovery that will change the way we think about loneliness, health, and what it means to fall in and out of love"--